Improvement of Medical Imaging Equipment Management in public hospitals of Bangladesh - Md. Anwar, Hossain; Mohiuddin, Ahmad, Prof. Dr. Engr.; Md. Rafiqul, Islam, Dr.; Mohd. Abdur, Rashid, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/